Rancangan Fixture Kursi Roda Untuk Pengguna Kursi Roda - Basrul Muhid, Muhammad; Subkhan, Subkhan; Yunus, Muhammad (Jurnal Inovasi Teknologi Terapan, 2026)
Mobility for persons with disabilities remains hindered by the lack of wheelchair-friendly transportation facilities, particularly in securing and stabilizing the wheelchair during travel. This study aims to design a wheelchair fixture system for Wheelchair User Vehicles using the VDI 2222 design method, which includes four main stages: planning, concept development, design, and finalization. Concept selection analysis was carried out using the Composite Performance Index (CPI) method, resulting in the optimal combination of a spring clamp, vertical bearing guide, and upper locking locator. Simulation using SolidWorks shows that the design can withstand a load of 657.05 N (65 kg) with a safety factor value of up to 3.000, indicating the system is safe and reliable. This design is expected to provide an innovative solution for disability-friendly vehicles with a lightweight, functional, and independently operable system.